Comparison of audio vs. audio + video for the rating of shared decision making in oncology using the observer OPTION5 instrument: an exploratory analysis - Michael R. Gionfriddo; Megan E. Branda; Cara Fernandez; Aaron Leppin; Kathleen J. Yost; Brittany Kimball; Gabriela Spencer-Bonilla; Laura Larrea; Katherine E. Nowakowski; Victor M. Montori; Jon Tilburt (BMC, 2018)
Abstract Background How non-verbal data may influence observer-administered ratings of shared decision making is unknown. Our objective for this exploratory analysis was to determine the effect of mode of data collection (audio+video vs. audio only) on the scoring of the OPTION5 instrument, an observer rated measure of shared decision making. Methods We analyzed recordings of 15 encounters between cancer patients and clinicians in which a clinical decision was made. Audio+video or audio only recordings of the encounters were randomly assigned to four trained raters, who reviewed them independently. We compared the adjusted mean scores of audio+video and audio only. Results Forty-one unique decisions were identified within the 15 encounters. The mean OPTION5 score for audio+video was 17.5 (95% CI 13.5, 21.6) and for audio only was 21.8 (95% CI 17.2, 26.4) with a mean difference of 4.28 (95% CI = 0.36, 8.21; p = 0.032). Conclusion A rigorous and well established measure of shared decision making performs differently when the data source is audio only. Data source may influence rating of observer administered measures of shared decision making. This potential bias needs to be confirmed as video recording to examine communication behaviors becomes more common.